Pedagang yang Amanah: Studi Eksplorasi Dengan Pendekatan Psikologi Indigenous - Ivan Muhammad Agung; Jhon Herwanto (Psympathic : Jurnal Ilmiah Psikologi, 2017)
Amanah is one important concept in the context of Indonesian society. Amanah is one admirable trait that should be owned by individuals, including trader. This study aims to explore the concept of the amanah of trader, as well as see the dynamics of the amanah of the trader. Number of participants were 142 people. This research used the Indigenous Psychology approach. An open-ended question was used as measuring instrument. The analysis showed that the amanah of the trader located on four issues, namely, benevolence, honesty, professional and positive character that were called by amanah belief. The society assess amanah of trader depends how amanah belief was formed on the trader that were influenced by individual factors (personality and cognitive process) and situational factors (institutional and social identity). Implications of the research results will be discussed in the context of Indigenous Psychology.